2007
DOI: 10.1016/j.otohns.2006.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Pepsin assay: A marker for reflux in pediatric glue ear

Abstract: Control of LPR may be an essential component in the successful management of OME in pediatric patients. Pepsin/pepsinogen analysis in effusions of children, using ELISA, can be considered a reliable marker for assessment of reflux in children with OME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
2
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 23 publications
1
80
2
4
Order By: Relevance
“…In adults, high pepsinogen levels of up to 95 times higher than that in serum were reported by Sone et al [14 ]. Abd El-Fattah et al [15 ] reported LPR in 71% of children with OME. They detected high levels of pepsinogen in middle ear effusions up to 231 times higher than serum levels, with a significant positive correlation between pepsinogen levels in the effusion and the number of LPR events.…”
Section: Laryngopharyngeal Reflux and Otitis Media With Effusionmentioning
confidence: 80%
“…In adults, high pepsinogen levels of up to 95 times higher than that in serum were reported by Sone et al [14 ]. Abd El-Fattah et al [15 ] reported LPR in 71% of children with OME. They detected high levels of pepsinogen in middle ear effusions up to 231 times higher than serum levels, with a significant positive correlation between pepsinogen levels in the effusion and the number of LPR events.…”
Section: Laryngopharyngeal Reflux and Otitis Media With Effusionmentioning
confidence: 80%
“…In patients with GORD, elevated levels of pepsin have recently been described in the respiratory epithelial lining fluid using EBC (Krishnan et al, 2007), using bronchoalveolar lavage (BAL; Farrell et al, 2006), and via the sampling of middle ear effusions of children with pharyngeal reflux (Abd El-Fattah et al, 2007; see Table 1). The advantage of analyzing pepsin is that it is not normally found in the lung and therefore should be specific for reflux.…”
Section: Novel Methods Of Diagnosing Gordmentioning
confidence: 99%
“…However, the middle ear pepsin concentrations far exceeded serum pepsin concentrations, indicating that the pepsin had not been concentrated in the middle ear cleft from serum [30]. Several other studies have duplicated this fi nding using a comparison of pepsin, albumin, and fi brinogen levels of ear samples with serum [33,39]. Lieu et al [34] found the gene encoding for pepsinogen I/A in two samples of gastric mucosa via reverse transcriptase polymerase chain reaction but not in separate discarded specimens from mastoid mucosa [34].…”
Section: Pepsin In the Middle Ear Space Has Gastric Originmentioning
confidence: 97%
“…El-Fattah et al [39] reported on 31 children with otitis media who had undergone 24-hour dual-probe pH testing, and pepsin was tested using direct ELISA in 17 children (mean age, 6.2 years) who underwent myringotomy with tube placement. Twenty-two children showed a positive pH probe study, indicating high prevalence of laryngopharyngeal refl ux in otitis media.…”
Section: Association Of Extragastric Pepsin Detection With Gerd or Eordmentioning
confidence: 99%